36 Enabling connections: using project ECHO (Extension of Community Healthcare Outcomes) in palliative care education. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Kelly, Anne; Andrew, Jane; Douglas, Claire
Abstract : Introduction: The need for palliative and end of life care is increasing in Scotland. Workforce development is required to support practitioners to be knowledgeable, skilled and confident in providing palliative care. Project ECHO is a validated, technology-enabled, educational approach used globally to connect networks of learners and form communities of practice. We were the first NHS Scotland palliative care service to use this model. The aims of our pilot project were To establish, deliver and evaluate ECHO groups as supportive communities of practice. To connect participants with tele–mentoring and support from Specialist Palliative Care services Methods: Project ECHO groups were established with community hospitals and care homes. Project ECHO uses a hub and spoke model. Each session comprises a formal teaching component, a case presentation brought by participants and facilitated case-based discussion. Evaluation was guided by a Logic Model aligned to Kirkpatrick's model 6 for educational evaluation. Mixed methods were used to gather evaluation data, including Survey Monkey, focus groups and reflective feedback. Results: All ECHO sessions were highly rated in terms of quality and utility. All participants reported increases in knowledge, skills and confidence. Participants shared reflective pieces highlighting integration of learning into practice and examples of improved patient care. Additional gains were through the building of relationships, greater understanding of other's perspectives and truly learning from and with each other. One year on, all Community Hospital sites remain engaged and their network has been extended. There is growing interest in Project ECHO within care homes. Conclusions: ECHO groups are of relevance and value to members. Project ECHO creates a rich educational environment which can support improved outcomes for patients in our communities. Virtual delivery provides significant savings and enabled the provision of ongoing education and support through Covid-19.